Galectin-3 Reflects Mitral Annular Plane Systolic Excursion Being Assessed by Cardiovascular Magnetic Resonance Imaging. (1st December 2016) - Kim, Seung-Hyun; Behnes, Michael; Natale, Michele; Hoffmann, Julia; Reckord, Nadine; Hoffmann, Ursula; Budjan, Johannes; Henzler, Thomas; Papavassiliu, Theano; Borggrefe, Martin; Bertsch, Thomas; Akin, Ibrahim
Abstract : Background . This study investigates whether serum levels of galectin-3 may reflect impaired mitral annular plane systolic excursion (MAPSE) in patients undergoing cardiac magnetic resonance imaging (cMRI). Methods . Patients undergoing cMRI during routine clinical care were included prospectively within an all-comers design. Blood samples for biomarker measurements were collected within 24 hours following cMRI. Statistical analyses were performed in all patients and in three subgroups according to MAPSE (MAPSE I: ≥11 mm, MAPSE II: ≥8 mm–<11 mm, and MAPSE III: <8 mm). Patients with right ventricular dysfunction (<50%) were excluded. Results . 84 patients were included in the study. Median LVEF was 59% (IQR 51–64%). Galectin-3 correlated significantly with NT-proBNP (r = 0.42, p = 0.0001 ). Galectin-3 increased significantly according to the different stages of impaired MAPSE (p = 0.006 ) and was able to discriminate both patients with impaired MAPSE <11 mm (area under the curve (AUC) = 0.645, p = 0.024 ) and <8 mm (AUC = 0.733, p = 0.003 ). Combining galectin-3 with NT-proBNP improved discrimination of MAPSE <8 mm (AUC 0.803, p = 0.0001 ). In multivariable logistic regression models galectin-3 was still associated with impaired MAPSE (MAPSE < 11 mm: odds ratio (OR) = 3.53, p = 0.018 ; MAPSE < 8 mm: OR = 3.18, p = 0.06 ). Conclusions . Galectin-3 reflects MAPSE being assessed by cardiac MRI.